Improving human rights in mental health takes more than just changing the law: An audit of medical assessments in regional community patients in Queensland. (April 2022) - Bateren, Verere; Callaghan, Sascha; Lan, Xinning; Nagra, Navjot; Rana, Ashish
Objective: To evaluate the medical assessments of involuntary community patients in a regional mental health service, determine the compliance with requirements under Queensland's Mental Health Act 2016 (the Act) to regularly review orders and assess patients' mental capacity. Method: We audited 183 patient records on community treatment authorities (CTAs) to determine whether medical assessments undertaken under the Act included consideration of the person's capacity, and regular reviews by an authorised doctor as required 1s205 . Results: The audit revealed that 51% of the CTA patients did not comply with legal requirements either to complete a capacity assessment and/or be medically assessed within three months of the last review. Conclusions: Over 50% of medical assessments did not comply with the legislative requirements to record capacity assessments and review involuntary treatment on at least a three-month basis. However, when the treatment criteria were met, it did not appear to be a basis for CTA revocation. Further research may help determine whether the Mental Health Review Tribunal (Tribunal) could play a greater role in overseeing compliance with the new legislative requirements or if other clinical oversight mechanisms would be appropriate to improve the assessment process.